Pengaruh Model Pembelajaran Contextual Teaching Learning Terhadap Hasil belajar Peserta Didik di SMA Hati Suci Jakarta Pusat - Yemima Dita Ria Habeahan; Nova Lina Sari Habeahan (LPPM Politeknik Pratama, 2023)
The research was intended to see the effect of the learning outcomes of the contextual teaching learning model with the type of pretest posttest control group experimental research. The study involved tenth grade students at Hati Suci High School, Central Jakarta as a population. The experimental class and control class were designed using cluster random sampling. Test as data collection by conducting a t test. The results of the analysis show the posttest analysis of the experimental class and the control class, namely 0.05, obtained t count 4.96 and t table 1.65, so t count > t table, the mean value is greater than the tests conducted for the experimental and control classes, the average class activity of students reached 76.22 with good criteria. Thus it can be concluded that the influence of the contextual teaching learning model influences the learning outcomes of class X students of SMA Hati Suci, Central Jakarta..